Assessing plain and intelligible language in the Consumer Rights Act: a role for reading scores? - Conklin, Kathy; Hyde, Richard; Parente, Fabio (Cambridge University Press, 2019)
Under the Consumer Rights Act 2015 consumer contracts and consumer notices are required to be expressed in plain and intelligible language. This is a difficult concept to capture. Determining whether a contract is expressed in plain and intelligible language involves resource intensive work by regulators and difficult adjudications by courts. This paper explores whether reading scores present a viable alternative. Can a simple computer program tell a consumer, a business, a regulator or the court that a particular contract is not expressed in plain and intelligible language? The paper begins by exploring the concept and role of plain and intelligible language in the Consumer Rights Act, before considering the ways that reading scores have developed and been used in legal contexts. We then report on the findings of an experimental examination of insurance contracts using a basket of reading scores, using our findings to draw conclusions about the utility of reading scores in determining whether a contract is expressed in plain and intelligible language. We find that reading scores can play a role in such determinations, but that further work is needed to provide appropriate tools for business, regulators and courts to use in assessing plain and intelligible language.